Genetic polymorphism of LHX4 gene and its association with growth and reproductive traits in goats of Odisha - CHANDANA SREE CHINNAREDDYVARI; DILLIP KUMAR KARNA; CHINMOY MISHRA; SUSANTA KUMAR DASH; SHANTIBHUSAN SENAPATI; LAKSHMAN SAHOO; BIKASH KUMAR BEHERA (Indian Journal of Animal Sciences)
The purpose of this study was to investigate the genetic variation in exon 6 of the LHX4 gene in Ganjam and Black Bengal goats. DNA was extracted from the buccal swab samples. By using specific primers, the target partial sixth exon of the LHX4 gene was amplified (382 bp). PCR amplification and DNA sequencing analysis revealed two non- synonymous transitions namely c.44997A>G and c.45028 C>A which caused a change in amino acid from histidine to glutamic acid and valine to isoleucine, respectively. Genotype frequencies in the Ganjam population were 0.32 and 0.68 for GG and AA genotypes, whereas the same in the Black Bengal population were 0.10 and 0.90 for GG and AA genotypes, respectively. The heterozygote GA genotype was missing in both populations and significantly deviated from the Hardy-Weinberg equilibrium. The Black Bengal goat had a significantly smaller body size than the Ganjam goat. Black Bengal goats had a significantly greater twinning percentage than the Ganjam breed. They also had a significantly lower age at sexual maturity (ASM), age at first kidding (AFK), and shorter kidding intervals (KI) than the Ganjam goats underscoring their superior reproductive potential. Except for chest girth, the effect of genotypes on body weight and morphometric traits was determined to be statistically non-significant. The effect of genotype was found to be non-significant on the reproductive traits.